IMPLEMENTASI PEMBELAJARAN DARING PADA MAHASISWA PGMI DI FAKULTAS TARBIYAH UIN AR-RANIRY - Syahidan Nurdin (FITRAH: International Islamic Education Journal, 2022)
The COVID-19 pandemic has changed almost everything, changing the way people live, including the world of education. Online learning is applied as a solution to meet the implementation of educational programs. In the PGMI Study Program, almost all courses are applied online and one of them is the Class Action Research course. This study aims to determine student perceptions of online learning in the Class Action Research course. The research method used is descriptive qualitative research method. The subjects in this study were all PGMI students and the sampling technique was snowball sampling. Data collection techniques were carried out by interviewing students. The results showed that online learning was well implemented. There were several obstacles found by students consisting of an unsupportive network, lack of library access, and inadequate learning environment conditions.